Anatomical parameters of Neck; Predictors for Laryngoscopy and Intubation - Kali kapoor; Rohit Kumar Varshney (Academia Anatomica International, 2017)
One of the common problems encountered by anaesthetists is difficult airway. Proper laryngoscopy and intubation is required by the anaesthetists for securing the airway by endotracheal tube. Anatomic parameters of the neck may prove to be a better predictors of airway particularly in difficult airway scenarios.